Between actor and critic : selected letters of Edwin Booth and William Winter - Watermeier, Daniel J.; Watermeier, Daniel J.; Watermeier, Daniel J. (Princeton University Press, 1971)
Sarah Bernhardt, London, his own acting-Edwin Booth commented on these and hundreds of other subjects in letters to William Winter, friend of twenty years and drama critic for the New York Tribune. Since he wrote neither autobiography nor diary, the letters constitute the fullest and most detailed record of Booth's career between 1869 and 1890, and arc a new and significant source of information about the actor.The 125 letters which Daniel Watermeier has selected and arranged in this volume are fully annotated; each is preceded by a headnote which provides an introduction to its content and narrative continuity from one letter to the next. Mr. Watermeier's introduction includes biographical sketches of Edwin Booth and William Winter and sets the context of their friendship.With few exceptions, the Booth-Winter letters have not hitherto been made public. They represent a major addition to studies of Edwin Booth and to the history of the American theater.Originally published in 1971.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Keywords: Booth, Edwin, -- 1833-1893.; Booth, Edwin, -- 1833-1893; BIOGRAPHY & AUTOBIOGRAPHY -- General.; PERFORMING ARTS -- Theater -- General.